Stability and vibration control of a flexible rotor-bearing system supported on oil-film bearings - Lim, Tau Meng (2008)
An algorithm to control the onset of instability due to oil-whirl is derived using eigenvalue loci relationship. Implementation of the technique on a simple Jeffcott-rotor supported on oil-film bearings ensures that oil-whirl does not occur within the desired operating speed is demostrated. A systematic and efficient approach for open and closed-loop adaptive control of flexible rotor-bearing system synchronous vibrations is presented.